Levels of Cognitive Control: A Functional Magnetic Resonance Imaging-Based Test of an RDoC Domain Across Bipolar Disorder and Schizophrenia - Smucny, Jason (Neuropsychopharmacology, 2018)
In recent years, the boundaries of psychopathology as defined by diagnostic categories have been criticized as inadequately ‘carving nature at its joints’ with respect to the neurobiology of major mental disorders. In 2010 the NIMH launched the Research Domain Criteria (RDoC) framework for understanding mental illnesses as brain circuit disorders that extend beyond DSM-defined diagnoses. In the present study we focus on cognitive dysfunction, a core feature of schizophrenia (SZ) and bipolar disorder (BPD), and use functional magnetic resonance imaging (fMRI) during a cognitive control (CC) task in recent onset patients to test the hypothesis that at a behavioral and underlying neural circuitry level these deficits exist on a continuum (as opposed to showing categorical differences) across the two disorders. In total, 53 healthy controls, 24 recent (<1 y) onset patients with BPD Type I with psychotic features, and 70 recent onset patients with SZ performed the AX-Continuous Performance Task while undergoing event-related fMRI at 1.5 T. In addition to behavior task-associated response was examined in frontoparietal regions-of-interest. In an a priori contrast-based analysis, significant deficits across patient groups (vs controls) were observed on CC-associated performance as well as frontoparietal response. These analyses further revealed a continuum of deficits in which BPD showed intermediate levels of CC relative to controls and SZ. Poor CC was associated with poverty and disorganization symptoms across patient groups. These results support the hypothesis that CC dysfunction in BPD and SZ reflects a continuum of deficits that cuts across traditional, DSM-based classification. Implications for the neurobiology of these diseases are discussed.